ENCAPSULATION OF HYPERICUM PERFORATUM L., JOJOBA OIL AND JASMINE OIL BY SPRAY DRYING AND THEIR APPLICATIONS IN TEXTILES - ÖGE Arzu; ERKAN Gökhan; SARIIŞIK A. Merih; ESER Burçin (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2017)
Microencapsulation is a technique that allows liquid or solid agents, such as pharmaceutical agents, pesticides, insect repellent agents, dyes, cosmetics and fragrances, to be encapsulated by a suitable barrier wall. Liquid or solid agents that are encapsulated are called core material. The importance of functional finishes have been increasing rapidly in the World. Microencapsulation is an alternative way to achieve the functional finishes because of their unique properties, such as controlled release, protection against to hazardous and destructive media, and providing higher surface area. In this study, jojoba, jasmine and St. John's Wort oils, were encapsulated according to spray drying method. St. John's Wort and jojoba oils were used at 1:1 ratio as fixed oil. Jasmine essential oil was added to fixed oil mixture at two different ratios. After preparing the core mixture, encapsulation studies were performed three different core : wall ratios. Morphological analyses of microcapsules were carried out using SEM (Scanning Electron Microscope). FTIR spectroscopy spectrums of microcapsules were determined (Fourier Transform Infrared). Particle size distribution microcapsules were analyzed by laser scattering measurement method. DSC (Differential Scanning Calorimetry) thermographs of microcapsules were obtained. All microcapsules were applied to 100% cotton knitted fabrics. Strength to washing of fabrics were observed by SEM micrographs.